(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
Climate change has been denied for decades and now many market players are making use of greenwashing, a form of misleading advertising, to appear green in the eyes of public opinion. This conduct, potentially prejudicial to consumers and competitors, directly refers to the private law clause of good faith. After clarifying the nature of greenwashing, the text delves into the admissibility of class action for redressing the damage caused to consumers and competitors. It then examines the practical usefulness of this approach in suppressing the phenomenon. Finally, possible legislative reactions are hypothesized with the aim of enhancing the deterrence of private enforcement remedies.